2018
DOI: 10.1002/asi.24035
|View full text |Cite
|
Sign up to set email alerts
|

Categorical relevance judgment

Abstract: In this study we aim to explore users' behaviour when assessing search results relevance based on the hypothesis of categorical thinking. In order to investigate how users categorise search engine results, we perform several experiments where users are asked to group a list of 20 search results into a number of categories, while attaching a relevance judgment to each formed category. Moreover, to determine how users change their minds over time, each experiment was repeated three times under the same condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Six search strings were used, each prefecture’s name ( n = 47) and one of the following health care information terms: “health system”, “hospital list”, “hospitals”, “emergency services”, “medical interpreters”, or “national health insurance.” These 282 search string combinations mimicked typical search query syntax [ 28 ]. The first three pages of search results (30 links) were assessed for inclusion with each search [ 29 ]; 8460 links were reviewed in total.…”
Section: Methodsmentioning
confidence: 99%
“…Six search strings were used, each prefecture’s name ( n = 47) and one of the following health care information terms: “health system”, “hospital list”, “hospitals”, “emergency services”, “medical interpreters”, or “national health insurance.” These 282 search string combinations mimicked typical search query syntax [ 28 ]. The first three pages of search results (30 links) were assessed for inclusion with each search [ 29 ]; 8460 links were reviewed in total.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the research in this area focuses on the relevancy of search engine results and has shown that individuals' assessments of relevancy tend to change over time. One common alternative to individual assessments of relevancy is to rely on the "wisdom of crowds" either through user studies or via click-through rates, which appears to improve the stability of relevancy judgments (Zhitomirsky-Geffet et al, 2016;Zhitomirsky-Geffet et al, 2018). Studies evaluating the information retrieval of library discovery tools have often relied on user observation in laboratory settings, log analysis or comparison of search results to student citations in particular projects or courses (Behnert and Lewandowski, 2017;Galbreath et al, 2021).…”
Section: Limitationsmentioning
confidence: 99%
“…For polarity classification, we convert the labeled data into three categories as done by Pang et al (2002). Like the categorical judgment given by Zhitomirsky‐Geffet, Bar‐Ilan, and Levene (2018), the reviews labeled with 1 and 2 stars are considered very negative and negative, whereas reviews with 4 and 5 stars are considered positive and very positive, and reviews with 3 stars are regarded as neutral (Pang et al, 2002). For this study, we confine our focus only on discriminating between positive and negative polarity sentiment.…”
Section: Experimental Evaluationmentioning
confidence: 99%